Development of Reading Skills and Systems for Working with Authentic Texts - Saida Nuritdinova (Researchparks Publishing, 2022)
The article deals with the issues of methods of formation of skills and abilities of the main types of reading. Reading is one of the factors for improving the quality of language training of students. The published material describes each type of reading for the development of perception, understanding and interpretation of authentic texts. The practical significance of the work lies in preparing students for intercultural communication, which is the main goal of teaching students a foreign language in educational institutions.